Wait a second! delayed impact of argument roles on on-line verb prediction. Issue 7 (9th August 2018) - Chow, Wing-Yee; Lau, Ellen; Wang, Suiping; Phillips, Colin
ABSTRACT: Comprehenders can use rich contextual information to anticipate upcoming input on the fly, but recent findings suggest that salient information about argument roles may not impact verb prediction. We took advantage of the word order properties of Mandarin Chinese to examine the time course with which argument role information impacts verb prediction. We isolated the contribution of argument role information by manipulating the order of pre-verbal noun phrase arguments while holding lexical information constant, and we examined its effects on accessing the verb in long-term semantic memory by measuring the amplitude of the N400 component. Experiment 1 showed when the verb appeared immediately after its arguments, even strongly constraining argument role information failed to modulate the N400 response to the verb. An N400 effect emerged in Experiment 2 when the verb appeared at a greater delay. Experiment 3 corroborated the contrast between the first two experiments through a within-participants manipulation of the time interval between the arguments and the verb, by varying the position of an adverbial phrase. These results suggest time is a key factor governing how diverse contextual information contributes to predictions. Here argument role information is shown to impact verb prediction, but its effect is not immediate.